Endobronchial ultrasound transbronchial needle aspiration in older people. Issue 4 (6th March 2013) - Okachi, Shotaro; Imai, Naoyuki; Imaizumi, Kazuyoshi; Hase, Tetsunari; Shindo, Yuichiro; Sakamoto, Koji; Aso, Hiromichi; Wakahara, Keiko; Hashimoto, Izumi; Ito, Satoru; Hashimoto, Naozumi; Sato, Mitsuo; et al.
<x xml:space="preserve">Abstract</x> Aim The usefulness and safety of endobronchial ultrasound transbronchial needle aspiration (EBUS‐TBNA) have been established recently, but no study has evaluated whether or not aging increases the risk of the procedure. In the present study, we aimed to assess the usefulness and safety of EBUS‐TBNA in older patients. Methods The medical records and database of 109 patients who received EBUS‐TBNA between 2008 and 2011 at Nagoya University Hospital, Nagoya, Japan were reviewed retrospectively. All patients underwent bronchoscopy under light sedation with midazolam. A total of 34 patients were aged 70 years or older (the older group) and 75 were aged 69 years or younger (the younger group). We analyzed patients' characteristics, changes of clinical parameters, usage doses of midazolam and lidocaine, procedure duration, geographic data of biopsied lymph nodes, diagnostic yield, and complications in both groups. Results There were more comorbidities in the older group. Four patients (11.8%) in the older group had poor performance status (2–3). Systolic blood pressure at baseline was significantly higher in the older group. There were no statistical differences between the two groups in some clinical parameters (minimum oxygen saturation [SpO2], reduction in SpO2, maximum oxygen supplementation, elevation of systolic blood pressure, increase of heart rate) during the procedure. Diagnostic performance in older patients was similar to that found in younger patients. There was no difference in the frequency of complications between both groups. Conclusion Safety and usefulness of EBUS‐TBNA in older people were comparable with those in younger people. Geriatr Gerontol Int 2013; 13: 986–992.